Telecommunications and Information Services for the Poor : Toward a Strategy for Universal Access - Navas-Sabater, Juan (Washington, DC: World Bank, 2013)
Access to information, and communications technologies has become crucial to a sustainable agenda of economic development, and poverty reduction, and yet access remains concentrated in a few regions and population groups, with the contours of this new "digital divide" closely following, and supplementing existing income, and economic divides. However, technological innovations, economic pressures, and regulatory reforms, are making access to information, and communications technologies more affordable, and, providing opportunities to close the digital divide. This discussion paper outlines a number of policy, and regulatory measures, including incentives to attract investors to high cost, or challenging areas, that can be used under different scenarios, to close the digital divide. While Bank Group experience shows an increasing number of projects with specific universal access components, this paper proposes alternatives for Bank Group support for universal access policies, through an appropriate mix of technical assistance, and investments.